PENGARUH PERENCANAAN KARIR ORGANISATIONAL DAN INDIVIDUAL TERHADAP KEPUASAN KERJA DAN KENERJA KARYAWAN - Sari, Desak Made Indah Paramitha; Wardana, I Made (Buletin Studi Ekonomi, 2019)
Abstract: The Effect of Organizational and Individual Career Planning on Job Satisfaction and Employee Performance. The aims of this research is to determine the influence of organizational and individual career planning to job satisfaction and employee performance PDAM Denpasar. The sample in this study was 135 people from PDAM Employees Denpasar that taken by proportional stratified random sampling method. The data analysis technique used is structural equation modeling (SEM) which computerized by using the program AMOS version 6. The results showed that organizational and individual career planning has positive and significant impact on employee job satisfaction PDAM Denpasar. Organizational career planning and individual influence on employee performance PDAM Denpasar and job satisfaction affects employee performance PDAM Denpasar. The implications of this research ;s to be repaired organizational and individual career planning and improvement of job satisfaction and employee performance PDAM Denpasar.